(untitled) (Książnica Śląska, 2025)
The subject of this article is functioning of memories about the Silesian Uprisings in social circulation. A significant role may be ascribed to stories of former insurgents, which, for the time distance, have undergone folclorization and fictionization (later events, for example from the period of the Second World War, have been introduced into narration). The memories, which had been formerly printed in anthologies, were realized as Filmowa encyklopedia powstań śląskich [The film encyclopedia of the Silesian Uprisings], a project in which the stories of insurgents’ life are told by their descendants. The knowledge about the Uprisings is also popularized with contests for young people, historical reconstructions, meetings and expositions. Finally, the author also remarks that the contemporary commemoration of historical events is dominated with ludic accents.